2019
DOI: 10.13080/z-a.2019.106.013
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and short-term N2O and CO2 emission from plant residue-amended soil with different fertilisation history

Abstract: The effect of biochar application on nitrous oxide (N 2 O) and carbon dioxide (CO 2 ) emissions from an arable soil amended with maize leaves was studied in a laboratory experiment using soil samples collected from plots with three different fertiliser treatments: no fertilisation (CONT), mineral fertiliser (NPKMg) and farmyard manure (FYM), of a well characterized agricultural experiment established in 1949. Two biochars (BC) used in the experiment were produced in low temperature slow (BC slow ) and in high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…At every air sampling occassion the plastic vessels were sealed for 20 minutes and air samples were collected from the headspaces with a syringe and transferred to pre-evacuated 12-ml glass vials (Labco Exetainer, Lampeter, UK). The same technique was used earlier in other experiments (Buchkina et al, 2019). The collected air samples were analyzed for N2O concentration using a gas chromatograph (GC-2010 Plus, Shimadzu) equipped with a 63 Ni electron capture detector (ECD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At every air sampling occassion the plastic vessels were sealed for 20 minutes and air samples were collected from the headspaces with a syringe and transferred to pre-evacuated 12-ml glass vials (Labco Exetainer, Lampeter, UK). The same technique was used earlier in other experiments (Buchkina et al, 2019). The collected air samples were analyzed for N2O concentration using a gas chromatograph (GC-2010 Plus, Shimadzu) equipped with a 63 Ni electron capture detector (ECD).…”
Section: Methodsmentioning
confidence: 99%
“…According to Bruun et al (2012), application of fast pyrolysis biochar (produced from wheat straw) resulted in immobilization of soil N (43%) during the 65-day incubation, while application of slow pyrolysis biochar led to net N mineralization (7%) in soil. Application of biochar can be considered as one of the useful ways of mitigating N2O emissions from soils (Buchkina et al, 2019;Horák et al, 2017;Ippolito et al, 2012;Rizhiya et al, 2019;Wang et al, 2013;Zhang et al, 2021). Biochar-induced improvement of soil physical and hydro-physical properties may mitigate microbial process of denitrification, which is the main process of N2O production in soils (Wrage et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high concentration of stabile carbon (C) compounds, the biochar decomposes very slowly in the soil that enables the long-term removal of C from the nutrient cycles, thereby being beneficial for climate change mitigation (Sohi, 2012). Also it has been found that biochar inhibits the release of greenhouse gases from the soil, but it has not been confirmed by all studies (Cayuela et al, 2014;Feng, Zhu, 2017;Buchkina et al, 2019;Escuer-Gatius et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Our results support the idea that biochar cannot be considered as a universal tool for the reduction of N 2 O emissions.Agronomy 2020, 10, 109 2 of 17Biochar, a carbon-rich material produced from organic matter by heating under low oxygen conditions (pyrolysis) [17,18], has been proposed as an amendment that can improve soil conditions and increase crop yield, especially for soils with small cation exchange capacity and low organic carbon content and pH [19,20], but also reduce N losses through NO 3 − leaching and N 2 O emissions into the atmosphere [21].Recent meta-analyses have reported average reductions of N 2 O emissions for lab and field experiments between 32% and 54% [21-23] after biochar application. However, there are also studies indicating no effect from biochar application on N 2 O emissions [24][25][26][27] as well as increased emissions [28][29][30], and studies showing opposite outcomes by applying the same biochar to different soils [31][32][33].The mechanisms by which biochar amendment reduces N 2 O emissions are not completely understood [30], and different hypothesis have been proposed: NO 3 − immobilization by biochar [21], reduction of organic matter degradation and soil C mineralization, a reduction that increases as biochar production temperature increases [34], and alteration of the microbial denitrifying communities [35], including the increase in abundance of N 2 O reductase bacteria, resulting in a reduced the N 2 O:N 2 ratio [36], likely due to the increase of soil pH after biochar application [37,38]. Biochar can also sequester C [21,39,40], reducing available labile C, which is one of the factors controlling denitrification.On the other hand, it has been reported that biochar amendment can increase N 2 O emissions [33,41], what has been generally associated to an enhancement of nitrification [13,24].…”
mentioning
confidence: 99%
“…Recent meta-analyses have reported average reductions of N 2 O emissions for lab and field experiments between 32% and 54% [21-23] after biochar application. However, there are also studies indicating no effect from biochar application on N 2 O emissions [24][25][26][27] as well as increased emissions [28][29][30], and studies showing opposite outcomes by applying the same biochar to different soils [31][32][33].…”
mentioning
confidence: 99%